Impoliteness and Rudeness in Sawungkampret Comics by Dwi Koendoro - Ayu Ida Savitri (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Impoliteness and rudeness are two different terms although both of them refer to the similar offensive behaviour. The difference of those terms lays on the intention of the speaker in doing the offensive behaviour. Culpeper (1996) introduces Impoliteness Theory as something he calls the parasite of Brown and Levinson’s (1987) Politeness Theory by exposing five super strategies: Bald on Record Impoliteness, Positive Impoliteness, Negative Impoliteness, Sarcasm or Mock Impoliteness, and Withhold Politeness. Furthermore, he divides impoliteness into three types: Affective, Coercive, and Entertaining Impoliteness. Meanwhile, rudeness is defined as what a speaker said or did –or even not said and done– which offends a hearer and prevents him/her to feel comfortable or convenience with the speaker’s words or acts. (Rondina and Workman, 2005:3). It is a kind of negative behaviour which is insensitive or disrespectful reflecting someone’s disregard towards others (Dubrin, 2011:87). In relation with Brown and Levinson (1987) Face Threatening Act (FTA), Beebe (1995) defines rudeness as “an FTA or features of FTA” breaking social interaction norms of the social context of it (in Culpeper, 2011:19). Culpeper (2005) himself considers impoliteness is done either intentionally or accidentally because impoliteness comes about when: (1) a speaker intentionally hold face-attack communication, or (2) a hearer assumes and/or considers a particular behaviour as “intended face-attacking”, or a combination of (1) and (2)” (in Bousfield and Locher, 2008:131). According to Segara (2007:141), rudeness happens when someone disregard and disobey the proper social manners with discourteous intention. It can be said that impoliteness is intentionally or accidentally occurs because of the hearer’s linguistics’s incompetence, while rudeness is intentionally happens to offend the hearer whether he/she gets offended or not. This research is done to show the difference of impoliteness and rudeness by using Sawungkampret Comics created by Dwi Koendoro as data source to get the sample of impoliteness and rudeness. The result shows that impoliteness can be done intentionally or not depending on what a speaker wants to show with his/her impoliteness, the hearer himself/herself gets the effect of impoliteness, and it is mainly used linguistics component. On the other hand, rudeness is done intentionally to show the speaker’s want, the hearer and people around him/her get the effect of rudeness, and it uses linguistics component along with culture and the sense of humanities embedded in it.